Mechanism of fat, oil and grease (FOG) deposit formation in sewer systems - Husain, Iman A. F.; Al-Khatib, Ma'an Fahmi Rashid; Jami, Mohammed Saedi; Mirghani, Mohamed Elwathig Saeed; Zainudin, Zaki; Hoda, Asif (AENSI Publications, 2014)
Fat, oil, and grease (FOG) released into sewer systems results in a continuous build-up and subsequent blockage of sewer pipes. Currently, scientist, authorities and wastewater municipalitieshave a lack of comprehensive understanding of the mechanism of FOG deposit formation and the factors influencing the deposition. In this study, the mechanism of FOG deposit formation is investigated. FOG deposits and wastewater samples were collected from a sewer pipe and characterized in the laboratory to determine its physical and chemical properties. The results showed that the deposits mainly constitute of FFAs, FOG, metals and metallic soaps of FOG, while there is a high amount ofpalmitic (C16) and oleic (C18)free fatty acids indicating the preference for hydrolysis reaction. The investigation of the site and the samples characterization justified the occurrence of the saponification reaction in the sewer pipes.